Cosmogony in a nutshell, or an attempt at analysing 95 strophes of the Atmopadeśa Śatakam of Narayana Guru - Urbańska, Hanna (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2015)
Narayana Guru, one of the Advaita Vedanta contemporary representatives in Kerala. This article is devoted to the concept of cosmogony in the works of Narayana Guru, which were compressed in an intriguing and enigmatic manner in one of the last strophes of this philosopher’s most importanat poem, the Atmopadeśa Śatakam (AŚ 95).
Keywords: Indian philosophy; Advaita Vedanta; Narayana Guru; Kerala